Community Satisfaction on The Utilization of E-health Information System in Surabaya City - Martha, Tiara Sandi Ayu Diea; Rochmah, Thinni Nurul (Universitas Negeri Semarang, 2021)
E-health is an online patient registration tool at the Primary Health Centre in Surabaya City. Monitoring the level of community satisfaction is needed to ensure that e-health continues to function properly. This study aims to determine the level of community satisfaction on the utilization of e-health information systems in Surabaya City and what factors influence it. The design of this research is associative with a quantitative approach. Data was collected using a questionnaire online with an accidental sampling technique on 385 respondents. Data analysis is using statistical descriptive and multiple linear regression tests. The results of this study indicate that most users are very satisfied with the e-health information system. Age (p=0018), gender (p=0.000), and sources of information (p=0.000) influenced community satisfaction on the utilization of e-health information systems. Based on these results, it is necessary for the government to maintain the quality of e-health and make e-health as a pilot for other cities or regions in Indonesia.